2006
DOI: 10.1158/0008-5472.can-05-0425
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Mediated Cisplatin Resistance in Ovarian Cancer: Modulation of p53 Action on Caspase-Dependent Mitochondrial Death Pathway

Abstract: Akt is a determinant of cisplatin [cis-diammine-dichloroplatinum (CDDP)] resistance in ovarian cancer cells, and this may be related to the regulation of p53. Precisely how Akt facilitates CDDP resistance and interacts with p53 is unclear. Apoptotic stimuli induce second mitochondria-derived activator of caspase (Smac) release from mitochondria into the cytosol, where it attenuates inhibitor of apoptosis proteinmediated caspase inhibition. Whereas Smac release is regulated by p53 via the transactivation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
209
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(224 citation statements)
references
References 42 publications
14
209
1
Order By: Relevance
“…Immunoblotting analysis of cytoplasmic fraction revealed that expression of constitutively active Akt reduced HtrA2/Omi release from the mitochondria into the cytosol more than 1 fold (Fig. 6C), which is consistent with a recent report (40) showing inhibition of HtrA2/Omi release by expression of constitutively active Akt2 in A2780S cells. Taken collectively, we conclude that Akt abrogates HtrA2/Omi pro-apoptotic function through phosphorylation of serine 212 in cytoplasm and inhibition of its release from the mitochondria (Fig.…”
Section: Akt Abrogates Htra2/omi Pro-apoptotic Function Through Phospsupporting
confidence: 92%
“…Immunoblotting analysis of cytoplasmic fraction revealed that expression of constitutively active Akt reduced HtrA2/Omi release from the mitochondria into the cytosol more than 1 fold (Fig. 6C), which is consistent with a recent report (40) showing inhibition of HtrA2/Omi release by expression of constitutively active Akt2 in A2780S cells. Taken collectively, we conclude that Akt abrogates HtrA2/Omi pro-apoptotic function through phosphorylation of serine 212 in cytoplasm and inhibition of its release from the mitochondria (Fig.…”
Section: Akt Abrogates Htra2/omi Pro-apoptotic Function Through Phospsupporting
confidence: 92%
“…Bax promotes apoptosis by enhancing the release of mitochondrial proteins including cytochrome c and Smac/DIABLO. Through transcription-independent pathways, p53 has a direct apoptogenic role where it translocates to mitochondria in response to cellular stress, resulting in apoptosis via interaction with antiapoptotic Bcl-2 and Bcl-X L proteins that alter the mitochondrial membrane potential and induce cytochrome c and Smac release into the cytosol with resultant caspase activation (72,75).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Upon release from mitochondria, AIF and EndoG translocate to the nucleus where they cause DNA fragmentation, 16,17 provoking apoptosis in a caspase-independent manner. 24,25 Cisplatin also has been shown to induce apoptosis through the mitochondrial release of proapoptotic molecules, including cytochrome c, [26][27][28] Omi/HtrA2, 29 Smac/Diablo, 30,31 and AIF. 19,30 However, the mechanisms by which cisplatin initiates apoptosis in cancer cells are not completely understood.…”
Section: Introductionmentioning
confidence: 99%